m6A modification on the fate of colorectal cancer: functions and mechanisms of cell proliferation and tumorigenesis - Jiang, Xiaohan; Jin, Ziyao; Yang, Yuzhong; Zheng, Xiang; Chen, Shaohua; Wang, Shuaijie; Zhang, Xuemei; Qu, Nanfang (Frontiers in Oncology, 2023)
N6-methyladenosine (m6A) is the most pervasive RNA modification in eukaryotic cells. The dynamic and reversible m6A modification of RNA plays a critical role in the occurrence and progression of tumors by regulating RNA metabolism, including translocation, mRNA stability or decay, pre-mRNA splicing, and lncRNA processing. Numerous studies have shown that m6A modification is involved in the development of various cancers. This review aims to summarize the significant role of m6A modification in the proliferation and tumorigenesis of CRC, as well as the potential of modulating m6A modification for tumor treatment. These findings may offer new therapeutic strategies for clinical implementation of m6A modification in CRC in the near future.